Determinan Sosial Ekonomi Kekerasan Seksual Anak dan Implikasinya terhadap Pembangunan SDM Kabupaten Halmahera Timur - Satulwahidah, Anis; Amin, Chairullah; Hidayah, Nurul (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Child sexual violence threatens health, educational continuity, psychological well-being, and the future productivity of children. This study examines the association of education, economic vulnerability, family parenting, and child-protection socialization with recorded sexual-violence cases and discusses the implications for human resource development in East Halmahera Regency. A quantitative explanatory design was applied to a balanced panel of ten subdistricts observed from 2021 to 2025, producing 50 observations. Model selection used the Chow, Breusch-Pagan Lagrange Multiplier, and Hausman tests. Descriptive data show that all reported violence cases increased from 9 cases in 2021 to 51 cases in 2025. During the five-year period, 182 victims were recorded, including 140 female children, while sexual violence accounted for 127 cases. Maba recorded 32 sexual-violence cases, followed by Maba Tengah and Kota Maba with 24 cases each. The tests selected the Random Effects Model. Economic vulnerability was the only variable significantly associated with recorded sexual-violence cases (coefficient = -0.583898; p = 0.0012). Education, parenting, and child-protection socialization had negative but statistically insignificant coefficients. The variables were jointly significant (Chi-square = 14.4438; p = 0.0060). The negative coefficient of the economic proxy requires cautious interpretation because the dependent variable reflects reported cases and child-specific sexual-violence data were not uniformly available for all years. The findings support integrated policies that connect family economic resilience, school and community prevention, safe reporting, victim recovery, and improved subdistrict-level data systems.